THE EFFECTIVENESS OF GOVERNMENT SOCIAL ASSISTANCE ON COMMUNITY ECONOMIC IMPROVEMENT AND COMMUNITY SATISFACTION HIGH CLICK AFFECTED BY COVID-19 PANDEMIC - Rudy Sentosa Rajagukguk, Frederik; Handayani Harahap, Hastuti (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
This study tries to answer the research objectives, namely to find out to determine the effectiveness of the assistance provided by the government to stabilize the community's economy and community satisfaction, especially SMEs in Tebing Tinggi City. The research method used is a quantitative method using SPSS version 25.00 which was collected from the results of distributing questionnaires to MSME actors in the city of Tebing Tinggi who received social assistance as many as 97 respondents. The analytical method used in this study is to use an instrument test, namely the validity and reliability test. The classical assumption test is the normality test, the multicolonearity test, the heteroscedasticity test, simple linear regression analysis, the hypothesis test, namely the T test. The results of SPSS in this study are that social assistance has an effect on improving the community's economy and community satisfaction, especially for SMEs in Tebing Tinggi City.